A high-throughput screening assay for distinguishing nitrile hydratases from nitrilases - Angelini, Leticia Mara Lima [UNESP]; Silva, Amanda Ribeiro Martins da [UNESP]; Rocco, Lucas de Freitas Coli [UNESP]; Milagre, Cintia Duarte de Freitas [UNESP] (Soc Brasileira Microbiologia, 2015)
A modified colorimetric high-throughput screen based on pH changes combined with an amidase inhibitor capable of distinguishing between nitrilases and nitrile hydratases. This enzymatic screening is based on a binary response and is suitable for the first step of hierarchical screening projects.
Keywords: Nitrile hydratase; Amidase; Nitrilase; Amidase inhibitor; High-throughput screening